2004
DOI: 10.2337/diabetes.53.6.1517
|View full text |Cite
|
Sign up to set email alerts
|

Islet Secretory Defect in Insulin Receptor Substrate 1 Null Mice Is Linked With Reduced Calcium Signaling and Expression of Sarco(endo)plasmic Reticulum Ca2+-ATPase (SERCA)-2b and -3

Abstract: Mice with deletion of insulin receptor substrate (IRS)-1 (IRS-1 knockout [KO] mice)show mild insulin resistance and defective glucose-stimulated insulin secretion and reduced insulin synthesis. To further define the role of IRS-1 in islet function, we examined the insulin secretory defect in the knockouts using freshly isolated islets and primary ␤-cells. T he insulin/IGF-1 receptor signaling pathway plays a significant role in the regulation of both insulin secretion and synthesis (1-5). We and other laborato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
62
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(71 citation statements)
references
References 73 publications
9
62
0
Order By: Relevance
“…Defects in glucose-stimulated calcium mobilisation are thought to be a component of this abnormality. For example, Insr-, Igf1r-and Irs1-deficient islets display reduced increases in intracellular calcium flux, which, in the case of Irs1-null islets, are thought to be in part due to decreased expression of sarco(endo)plasmic reticulum Ca 2+ -ATPase expression [7,26,27]. PIrs2KO beta cells also showed impaired calcium mobilisation in response to glucose, suggesting that IRS2 signalling is also a component of this mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Defects in glucose-stimulated calcium mobilisation are thought to be a component of this abnormality. For example, Insr-, Igf1r-and Irs1-deficient islets display reduced increases in intracellular calcium flux, which, in the case of Irs1-null islets, are thought to be in part due to decreased expression of sarco(endo)plasmic reticulum Ca 2+ -ATPase expression [7,26,27]. PIrs2KO beta cells also showed impaired calcium mobilisation in response to glucose, suggesting that IRS2 signalling is also a component of this mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…The link between insulin signaling and secretion has been demonstrated in IRS1 knockout (KO) mice, which show marked insulin secretory defects in response to glucose and reduced insulin synthesis (Kulkarni et al 1999), and in IRS2 KO mice, which primarily show a decrease in -cell mass (Withers et al 1998). More recently, the defective glucose sensing in IRS1 KO mice was found to be associated with impaired intracellular Ca 2+ signaling (Kulkarni et al 2004). Based on these observations, it is possible that the higher basal activity of the IRSs-PI3K cascades partly mediates -cell growth and improves insulin secretion in pregnant rats.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that Ca 2C handling in pancreatic b-cells plays an important role in the regulation of insulin secretion. Diminished SERCA expression and activity has been described as a common dysfunction related to the poor insulin secretion observed in animal models of diabetes (Roe 1994, Varadi et al 1996, Levy et al 1998, Marie et al 2001, Kulkarni et al 2004. Although both SERCA2 and SERCA3 isoforms are co-expressed in human and rat islets and in the RINm5F b-cell line (Varadi et al 1996), several studies have suggested a central role for SERCA3 in b-cell function.…”
Section: Discussionmentioning
confidence: 99%
“…-ATPase (SERCA) activity and expression, has been suggested as the cause of impaired insulin secretion in several animal models of glucose intolerance (Marie et al 2001, Kulkarni et al 2004, including the db/db mice (Roe et al 1994). db/db Mice display obesity and type 2 diabetes, due to the absence of functional leptin receptors, the main activator of STAT3 in pancreatic b-cells (Shafrir 1992, Morton et al 1999.…”
Section: Cmentioning
confidence: 99%